Examining the relationships among service quality, satisfaction and revisit intention to Sarawak Regatta / Nuraimi Othman - Othman, Nuraimi (2014)
Sport tourism event can be differentiated from other events by looking at the basis of service provided. Research in measuring the service quality is important as it can provide strategies that would maximize efficiency and effectiveness in managing spectators’ satisfaction in the context of sports tourism event. This study examines and extends the empirical evidence of the relationships among the dimensions of service quality, spectators’ satisfaction and revisit intention. A new measurement model was developed, namely Sport Tourism Event Quality (STEQ) that links to examine the service quality relationship with spectators’ satisfaction and revisit intention. Confirmatory Factor Analysis (CFA) was performed to assess the validity and reliability of this instrument to examine the proposed dimensional structure. The STEQ comprises five dimensions of service quality: venue accessibility, crowd, security, contest and accommodation. Correlation and regression analyses were employed to examine the relationships among the five constructs. Using purposive sampling, data were collected from spectators (n = 372) who visited Kuching Waterfront to watch Sarawak Regatta. Crowd and venue accessibility was found to have the strongest relationship with spectators’ satisfaction. However, spectators’ satisfaction partially mediates the relationship between STEQ and revisit intention. This study has shown that the new measurement model of STEQ significantly explains spectators’ satisfaction and revisit intention to sports event. The finding of the present study provides methodological contributions and practical implications for further understanding of service quality in the context of sport event tourism.